2017
DOI: 10.1038/s41598-017-05716-z
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-derived IL-33 promotes intestinal tumorigenesis in Apc Min/+ mice

Abstract: Increased expression of Interleukin (IL)-33 has been detected in intestinal samples of patients with ulcerative colitis, a condition associated with increased risk for colon cancer, but its role in the development of colorectal cancer has yet to be fully examined. Here, we investigated the role of epithelial expressed IL-33 during development of intestinal tumors. IL-33 expression was detected in epithelial cells in colorectal cancer specimens and in the Apc Min/+ mice. To better understand the role of epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 71 publications
4
79
0
Order By: Relevance
“…For CD4 + T-cell isolation, mLNs and large intestine were digested in collagenase as described previously 27 . CD4 + T cells were enriched by positive immunoselection using CD4-(L3T4) microbeads (Miltenyi Biotec).…”
Section: T Cell Purificationmentioning
confidence: 99%
“…For CD4 + T-cell isolation, mLNs and large intestine were digested in collagenase as described previously 27 . CD4 + T cells were enriched by positive immunoselection using CD4-(L3T4) microbeads (Miltenyi Biotec).…”
Section: T Cell Purificationmentioning
confidence: 99%
“…This led to the novel finding that Sprouty2 deletion induces IL-33 production in colonic epithelial cells. IL-33 is expressed by epithelial, stromal, and immune cells, though at homeostasis, epithelial expression is normally low 49,50 . IL-33 regulation has predominantly been studied in immune cells 51 and control of its expression in the intestinal epithelial compartment is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study using engineered mice model has shown that epithelial-derived IL-33 increases ST2 1 regulatory T cells population, Th2 cytokines production and M2 macrophages infiltration to promote gut tumorigenesis. 38 Soluble ST2 has been shown to act as a decoy receptor to disrupt the signaling transduced by IL-33 to its membrane-bound receptor, ST2. 11,15,35 Consistently, we found that knockdown of sST2 in tumor cells displayed an in vivo growth advantage compared to control group (Fig.…”
Section: Discussionmentioning
confidence: 99%